2019
DOI: 10.15252/embj.201899984
|View full text |Cite
|
Sign up to set email alerts
|

Atoh1 + secretory progenitors possess renewal capacity independent of Lgr5 + cells during colonic regeneration

Abstract: During homeostasis, the colonic epithelium is replenished every 3–5 days by rapidly cycling Lgr5+ stem cells. However, various insults can lead to depletion of Lgr5+ stem cells, and colonic epithelium can be regenerated from Lgr5‐negative cells. While studies in the small intestine have addressed the lineage identity of the Lgr5‐negative regenerative cell population, in the colon this question has remained unanswered. Here, we set out to identify which cell(s) contribute to colonic regeneration by performing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 43 publications
2
61
1
Order By: Relevance
“…In support of this notion, another study demonstrated that NEUROG3+ cells not only give rise to EECs but surprisingly also to non-EEC cells, which suggests these progenitors can dedifferentiate to produce other lineages (Schonhoff et al, 2004). Additional recent studies have shown that ATOH1+ common secretory progenitors can dedifferentiate into a multipotent stem-like state spontaneously and in response to intestinal injury (Tomic et al, 2018) (Castillo-Azofeifa et al, 2019. In agreement with these studies our trajectory analyses predict that while the vast majority of EEC progenitors are stable, a small fraction is predicted to dedifferentiate.…”
Section: Discussionmentioning
confidence: 87%
“…In support of this notion, another study demonstrated that NEUROG3+ cells not only give rise to EECs but surprisingly also to non-EEC cells, which suggests these progenitors can dedifferentiate to produce other lineages (Schonhoff et al, 2004). Additional recent studies have shown that ATOH1+ common secretory progenitors can dedifferentiate into a multipotent stem-like state spontaneously and in response to intestinal injury (Tomic et al, 2018) (Castillo-Azofeifa et al, 2019. In agreement with these studies our trajectory analyses predict that while the vast majority of EEC progenitors are stable, a small fraction is predicted to dedifferentiate.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, cellular plasticity has been proved in several lineages residing above the crypt base and contributes to intestinal regeneration. Dll1 + or Atoh1 + secretory progenitors and Alpi + enterocyte progenitors have been shown to possess renewal capacity and were able to compensate for the complete ablation of Lgr5 + cells under physiological or regenerative conditions ( Castillo-Azofeifa et al., 2019 ; Tetteh et al., 2016 ; van Es et al., 2012 ). Another recent study showed that the post-IR regeneration of intestinal epithelium preferentially went through the activation of crypt Clu + cells rather than the recruitment of depleted Lgr5 + cells ( Ayyaz et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, distinguished from the slow-cycling Hopx + stem cells that display a constant Hopx expression identified by Takeda et al, Hopx + CARSCs display a transient discontinuation of Hopx expression upon injury and then proliferate to reestablish the colon architecture. The secretory progenitor cells marked by the transcription factor Atoh1 have also been shown to repopulate the colonic epithelium during DSS-induced colitis (Castillo-Azofeifa et al 2019 ; Ishibashi et al 2018 ; Tomic et al 2018 ). Therefore, it would be interesting to know if Atoh1 + progenitors overlap with Hopx + CARSCs.…”
Section: Quiescent Stem Cellsmentioning
confidence: 99%